Mechanism suppressing charge recombination at iodine defects in CH3NH3PbI3 by polaron formation. Issue 35 (28th August 2018) - Wiktor, Julia; Ambrosio, Francesco; Pasquarello, Alfredo
Abstract : Polaron formation prevents the hole trapping at the negatively charged iodine interstitial in CH3 NH3 PbI3 . Abstract : Metal-halide perovskites exhibit high efficiencies in photovoltaic applications and low recombination rates, despite the high concentrations of intrinsic defects. We here study the hole trapping at the negative iodine interstitial, which corresponds to the dominating recombination center in CH3 NH3 PbI3 . We calculate the free energy profile for the hole trapping at 300 K using the Blue Moon technique based on hybrid functional molecular dynamics. We find that the hole trapping is energetically unfavorable and requires overcoming an energy barrier. This behavior stems from the position of the vertical (−/0) transition level of the iodine defect and the formation of a polaron. Our simulations show that the polaron does not interact with the iodine interstitial and hops through the lattice on a sub-picosecond scale. Our results highlight a mechanism by which the low mononuclear (trap-assisted) recombination rates in CH3 NH3 PbI3 can be explained.